Revision of world Ooderella Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae), with description of the first males for the genus - Gibson, Gary A. P. (Zootaxa, 2017)
The world species of Ooderella Ashmead, 1896 are revised. Characterization of the genus is based primarily on females, but for the first time males are associated with females through collecting events and described for four species. Putative generic features of males as well as morphological limits of both sexes are discussed, as are possible infrageneric relationships. Previously consisting of a single species from South America, Ooderella smithii Ashmead (♀, ♂), 18 new species are described from the Neotropical, Nearctic and Afrotropical regions, including one from the Nearctic region [O. americana n. sp. (♀)], 5 from the Afrotropical region [O. botswanae n. sp. (♀), O. capensis n. sp. (♀), O. gymnosoma n. sp. (♀), O. kenyaensis n. sp. (♀), and O. platyscapus n. sp. (♀, ♂)], and 12 from the Neotropical region [(O. ambigua n. sp. (♀), O. flavida n. sp. (♀), O. hansoni n. sp. (♀), O. hyalipleura n. sp. (♀), O. melanosceles n. sp. (♀), O. microptera n. sp. (♀), O. reticulifrons n. sp. (♀), O. setosa n. sp. (♀, ♂), O. speculifrons n. sp. (♀), O. spinositegula n. sp. (♀, ♂), O. stenoptera n. sp. (♀), and O. thegalea n. sp. (♀)]. The species are keyed, described, illustrated through macrophotography, and their distributions mapped.